2021
DOI: 10.1186/s13756-021-00918-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends, risk factors and outcomes of infections due to extended-spectrum β-lactamase producing Enterobacterales in Swiss solid organ transplant recipients between 2012 and 2018

Abstract: Background The burden of antimicrobial resistance is high in solid organ transplant (SOT) recipients. Among Swiss SOT recipients, we assessed temporal trends of ESBL-producing Enterobacterales (ESBL-E), identified risk factors for ESBL-E, and assessed the impact of resistance on patient outcome. Methods Data from the Swiss Transplant Cohort Study (STCS), a nationwide prospective cohort of SOT-recipients, were analysed. Temporal trends were describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The higher rate of MDR infections in SOT has been attributed to their frequent antibiotic exposure (e.g., from post‐transplant antimicrobial prophylaxis regimens and increased susceptibility to infections) 1,23 . Interestingly, MDR GNB was not significantly associated with mortality among our SOT recipients, in contrast to other reports 42,43 . Aggressive, broad‐spectrum empiric antibiotic administration at the first signs of sepsis in our SOT recipients, or possibly the administration of prolonged courses of antibiotics could explain this observation.…”
Section: Discussioncontrasting
confidence: 48%
“…The higher rate of MDR infections in SOT has been attributed to their frequent antibiotic exposure (e.g., from post‐transplant antimicrobial prophylaxis regimens and increased susceptibility to infections) 1,23 . Interestingly, MDR GNB was not significantly associated with mortality among our SOT recipients, in contrast to other reports 42,43 . Aggressive, broad‐spectrum empiric antibiotic administration at the first signs of sepsis in our SOT recipients, or possibly the administration of prolonged courses of antibiotics could explain this observation.…”
Section: Discussioncontrasting
confidence: 48%
“…A further study analyzing the etiology of post‐transplant BSI in a Spanish center detected an increasing rate of ESBL‐producing strains, mainly K. pneumoniae , from 7% in the period 2007–2008 to 34% in 2015–2016 2 . A nationwide study carried out in Switzerland reported that the proportion of ESBL‐E infections in SOT recipients rose in recent years to 11.4%, although the proportion of ESBL produces among E. coli isolates remained stable over time (in contrast to the increasing trend observed for non‐ E. coli strains) 18 …”
Section: Esbl‐e Infections After Sot: Epidemiology Molecular Characte...mentioning
confidence: 98%
“…2 A nationwide study carried out in Switzerland reported that the proportion of ESBL-E infections in SOT recipients rose in recent years to 11.4%, although the proportion of ESBL produces among E. coli isolates remained stable over time (in contrast to the increasing trend observed for non-E. coli strains). 18 Risk factors for developing post-transplant ESBL-E infection include previous antibiotic exposure, pre-transplant colonization, perioperative prophylaxis, prolonged tracheal intubation, long-term hospitalization, urinary tract obstruction and instrumentation, kidneypancreas transplantation, post-transplant renal replacement therapy (RRT), and recurrent urinary tract infection (UTI), as reviewed elsewhere. 3,19 A recent multicenter case-control study in the USA comprising 988 ESBL-E BSI episodes identified various risk factors of relevance, including the isolation of ESBL-E in a prior culture, a corticosteroid-containing immunosuppression regimen, acute rejection treated with corticosteroids, and previous exposure to third-generation cephalosporins, echinocandins and trimethoprimsulfamethoxazole.…”
Section: Esbl-e Infections After Sot: Epidemiology Molecular Characte...mentioning
confidence: 99%
“…A subsequent publication detailed the epidemiology and risk factors of ESBL‐producing Enterobacterales. 12 Out of 1212 Enterobacterales infections, 138 (11%) were ESBL‐producing. The main risk factor for acquisition of ESBL‐producing Enterobacterales infection was a previous antibiotic exposure (aOR = 2.6, 95%‐CI: 1.0–6.8).…”
Section: Epidemiology Of Transplant‐infectious Diseases In Switzerlandmentioning
confidence: 99%
“…and Escherichia coli produced extended‐spectrum β‐lactamase (ESBL), but no infection due to carbapenemase‐producing bacteria was identified. A subsequent publication detailed the epidemiology and risk factors of ESBL‐producing Enterobacterales 12 . Out of 1212 Enterobacterales infections, 138 (11%) were ESBL‐producing.…”
Section: Epidemiology Of Transplant‐infectious Diseases In Switzerlandmentioning
confidence: 99%